(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In this article, the translation of Shakespeare’s works is a complex task, which poses a number of difficulties due to the linguistic, cultural and literary subtleties of his dramaturgy. The main difficulty lies in Shakespeare’s use of early modern English, characterized by archaic modern vocabulary, complex syntax, and rich vocabulary. Translators often report difficulties in finding equivalents in other languages ​​that reflect the wordplay, double meanings, and poetic nuances of the original.